2020
DOI: 10.1002/jbt.22558
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide attenuates cyclophosphamide‐induced hepatotoxicity in SD rats by reducing oxidative stress and apoptosis

Abstract: Cyclophosphamide (CP) is a widely used anticancer and immunosuppressant drug. Nevertheless, clinical utilization of CP is limited due to considerable adverse effects and toxicities. Nicotinamide (NMD) is a micronutrient and the effect of NMD against CPinduced hepatotoxicity is yet unexplored. The present study was designed to evaluate the chemoprotective effect of NMD against CP-induced hepatic injury in Sprague-Dawley rats. Hepatotoxicity was induced by the administration of CP (30 mg/kg/day) for 10 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…The cellular status of overwhelmed oxidative agents accompanied by decreased antioxidant contents is described as oxidative stress. As documented by many recent reports [ 5–7 , 10 , 18 ], oxidative stress in liver of CP-injected mice was evidenced in the present study by the increased level of MDA, protein carbonyl, and NO and by decreased GSH levels and antioxidant enzymes (SOD and CAT) activities. Increased lipid peroxidation causes alterations in membrane fluidity and membrane integrity, thus disrupting membrane permeability [ 57 ].…”
Section: Discussionsupporting
confidence: 84%
“…The cellular status of overwhelmed oxidative agents accompanied by decreased antioxidant contents is described as oxidative stress. As documented by many recent reports [ 5–7 , 10 , 18 ], oxidative stress in liver of CP-injected mice was evidenced in the present study by the increased level of MDA, protein carbonyl, and NO and by decreased GSH levels and antioxidant enzymes (SOD and CAT) activities. Increased lipid peroxidation causes alterations in membrane fluidity and membrane integrity, thus disrupting membrane permeability [ 57 ].…”
Section: Discussionsupporting
confidence: 84%
“…These data suggested the CK1A signaling partly explained the mechanism of NAM on the lens regeneration. In addition, NAM is best known in enhancing cell survival, improving reprogramming, facilitating differentiation, regulating DNA repair, suppressing apoptosis and promoting the development and self-renewal, which is a multifunctional factor [20,[41][42][43]. Therefore, we would repeat the in vitro lenses regeneration for RNAseq analysis and specific transgenic mouse models for better understanding of the…”
Section: Discussionmentioning
confidence: 99%
“…Despite of clinical applications of CP, it has adverse in uence on the liver that decomposes CP to active metabolites, on the kidney that excretes it. The previous studies have shown that impaired humoral secretion, infertility, DNA damage, lipid peroxidation and morphological defects in the tissues are associated to the treatment with the CP (Patwa & Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%